Awareness and prevention of HIV/AIDS among farming communities in Akinyele and Kajola Local Government Areas of Oyo State, Nigeria (2012)
This study was carried out to assess the-awareness and prevention of HIV/AIDS among members of farming communities in Akinyele and Kajola Local government Areas of Oyo State. The rationale for carrying out this research is to determine the level of knowledge and attitudes of the participants on HIV/AIDS, identify the level of awareness of prevention of HIV/AIDS among the participants, and to identify the channel through which the participants received their information on awareness and prevention of HIV/AIDS. Twenty-five participants’ each were purposively selected from each of twelve randomly selected communities from the two Local Government Areas to give a total of 300 respondents. Data for the study was collected through structured interview schedule. Data was analysed using frequency counts and percentages. Hypothesis tested were analysed using Pearson Product Moment Correlation (PFMC). Finding showed that majority of members of farming communities in the two Local Government were with primary six leaving certificate (low level of formal education) Radio was the major channel through which they received HIV/AIDS information 64% of the respondents indicated. None of the respondents received information through the posters 94% of the respondents received HIV/AIDS information on radio programme called "Abule Oloke Merin. All the respondents (100%) in the two Local government Area of study believe that anal sex should be avoided. They believed that sex should not be abstained (87.38%, and79.3%) disagreed with abstinence. The tested hypotheses indicated significant relationship between gender, educational, attainment and types of marriage of the respondents and their HIV/AIDS awareness.